O discurso de outrem em retextualizações - Rosa, Flávio Cesar Oliveira da (2011)
This work investigates features that speakers use to introduce different voices during retextualization of a literary work. It presents events revealing different resources used, characterizing the discursive heterogeneity, recognized through various brands such as quotation marks, italics, etc. The material analyzed, ie, the corpus of this research, consists of 65 essays from the reading of a literary work - Jealous of Card, Moacyr Scliar - produced by students of the 8th year of high school while in the classroom. The data revealed that the resource most used by students was the indirect discourse, although there also occurred the use of other resources such as free indirect discourse and modalizations in fewer redactions. Notably, the autonym connotation was noted through the use of quotation marks, and the use of parentheses. The recurrence of the parentheses seem to be justified by the need to make clearer sentences that could raise questions to the reader, since the protocol request retextualization established a thirty lines of text, which would certainly limit the possibilities of expansion of the text